2002
DOI: 10.1074/jbc.m205144200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Regulatory Sites of Phosphorylation of the Bovine Endothelial Nitric-oxide Synthase at Serine 617 and Serine 635

Abstract: and Ser 635 regulates eNOS activity and contributes to the agonist-stimulated eNOS activation process. Endothelial nitric-oxide synthase (eNOS)1 is an important enzyme in the cardiovascular system producing nitric oxide (NO), a key regulator of blood pressure, platelet function, and vessel remodeling. Endothelial NOS is regulated by multiple mechanisms involving both protein-protein interactions with several different proteins, including caveolin-1 and Hsp90 (1), and post-translational modifications that inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
181
1
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 193 publications
(196 citation statements)
references
References 29 publications
9
181
1
4
Order By: Relevance
“…Phosphorylation of T495 reduces eNOS activity through reduced calmodulin association and increased O 2 Ϫ production (12,18,29). S633 phosphorylation of eNOS increases eNOS activity in cultured cells and in enzyme activity assays (2,32). There was no significant difference in the level of eNOS PO 4 at T494 [T495(hum)] or S632 [S633(hum)] in OZR vs. lean controls.…”
Section: Discussionmentioning
confidence: 71%
“…Phosphorylation of T495 reduces eNOS activity through reduced calmodulin association and increased O 2 Ϫ production (12,18,29). S633 phosphorylation of eNOS increases eNOS activity in cultured cells and in enzyme activity assays (2,32). There was no significant difference in the level of eNOS PO 4 at T494 [T495(hum)] or S632 [S633(hum)] in OZR vs. lean controls.…”
Section: Discussionmentioning
confidence: 71%
“…eNOS phosphorylation as an activation mechanism was recognized only recently but the evidence supporting its importance has grown rapidly (Dimmeler et al, 1999;Fulton et al, 1999). Currently, 5 Ser/Thr residues (Ser116, Thr497, Ser617, Ser635 and Ser1179) are known to be phosphorylated by numerous protein kinases including PKA, protein kinase B (Akt), CaM kinase II, AMP-activated kinase and protein kinase C in response to physiological stimuli (Michell et al, 2002;. In our previous studies, the stimulation of PKA by treating BAECs with a cell-permeable cAMP analog, 8-Br-cAMP, was found to enhance the phosphorylation of eNOS at Ser635 and Ser1179 (Boo et al, 2002b).…”
Section: Resultsmentioning
confidence: 99%
“…It is currently viewed that while PKA phosphorylates eNOS at Ser1179 and Ser635, protein kinase B (Akt) phosphorylates Ser1179 and Ser617 in vitro and in cells (Dimmeler et al, 1999;Fulton et al, 1999;Butt et al, 2000;Boo et al, 2002a;Michell et al, 2002). Because both PKA and Akt can phosphorylate eNOS at Ser1179 in common, and they share consensus sequences, I further examined if the phospho-PKA substrate antibody detects eNOS phosphorylated by Akt.…”
Section: Resultsmentioning
confidence: 99%
“…However, several lines of evidence have shown that PKA also regulates the phosphorylation of eNOS at Ser 1179 , Ser 635 , and Ser 617 in bovine eNOS (Ser 1177 , Ser 633 , and Ser 615 in humans) [24,[26][27][28][29] . Ser 633/635 phosphorylation is critical in maintaining NO synthesis after the initial sensitization by Ca 2+ flux and Ser 1177/1179 phosphorylation [30] , and it is stimulated via the PKA pathway in response to shear stress and acute statin treatment in aortic endothelial cells [24,27] , suggesting that PKA-mediated Ser 633/635 phosphorylation may be another mechanism by which statins protect against myocardial no-reflow and necrosis after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%